A reflection and the future of health and safety in New Zealand - Bennett, Robyn (New Zealand Journal of Health and Safety Practice, 2025)
As we publish volume 2, edition 1 of the New Zealand Journal of Health and Safety Practice, it is an opportune moment to reflect on our journey and consider the future of our profession. The field of health and safety in New Zealand has seen significant advancements, driven by the most part through initiatives from the professions and the enthusiasm and passion of the health and safety community. It is important then that we celebrate our achievements, acknowledge the challenges, and envision the path ahead.